Real-world effectiveness of palbociclib in HR+/HER2- metastatic breast cancer: a literature review - Emilie Adrian Christiansen; Iben Kümler (Future Science OA)
Approximately 70% of newly diagnosed breast cancers are of the HR+/HER2- subtype. For the treatment of patients with HR+/HER2- metastatic breast cancer, current guidelines recommend the use of a CDK4/6 inhibitor (palbociclib, ribociclib or abemaciclib) in combination with endocrine therapy. In this review we assess existing literature concerning real-world effectiveness of palbociclib. Survival outcomes in terms of progression-free survival and overall survival are discussed and compared among the included real-world studies and in relation to the phase III PALOMA trials.